Thyroid Eye Disease (Springer Nature, 2025)
This open access book provides a comprehensive, open access reference on thyroid eye disease for healthcare professionals. It is structured for easy reference around the key topics in thyroid eye disease management, with sections on natural history and pathogenesis, diagnosis and investigation, medical management, surgical management and psychological impact. The support of Thyroid Eye Disease Charitable Trust ensures that the book includes consideration of patient-centered care throughout each chapter. Thyroid Eye Disease: A Collaborative Open Access Reference is an essential resource for ophthalmologists around the world (particularly oculoplastics specialists) as well as endocrinologists, nurses, optometrists and orthoptists.